+0  
 
+1
161
1
avatar

x = 2y -5

5x -6y = 7

sad

Guest Oct 24, 2017

Best Answer 

 #1
avatar+7067 
+1

x  =  2y - 5

 

5x - 6y  =  7        Since  x = 2y - 5 , we can substitute  2y - 5  in for  x .

5(2y - 5) - 6y  =  7           Distribute  5  to the terms in partenthesees.

10y - 25 - 6y  =  7            Add  25  to both sides of the equation.

10y - 6y  =  7 + 25           Combine like terms.

4y  =  32        Divide both sides by  4 .

y  =  8            Plug this value for  y  into the first equation to find  x .

 

x  =  2(8) - 5

x  =  16 - 5

x  =  11          smiley

hectictar  Oct 24, 2017
 #1
avatar+7067 
+1
Best Answer

x  =  2y - 5

 

5x - 6y  =  7        Since  x = 2y - 5 , we can substitute  2y - 5  in for  x .

5(2y - 5) - 6y  =  7           Distribute  5  to the terms in partenthesees.

10y - 25 - 6y  =  7            Add  25  to both sides of the equation.

10y - 6y  =  7 + 25           Combine like terms.

4y  =  32        Divide both sides by  4 .

y  =  8            Plug this value for  y  into the first equation to find  x .

 

x  =  2(8) - 5

x  =  16 - 5

x  =  11          smiley

hectictar  Oct 24, 2017

25 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.